The Effect of Organizational Communication and Work Environment on Employee Performance at PT. Kencana Sawit Indonesia (KSI) - Afriyeni, Afriyeni; Sari, Intan Permata (Bina Bangsa International Journal of Business and Management, 2023)
The porpuse of this research is to examine the directives of organizational communication and work environment variables on employee performance at PT. Kencana Sawit Indonesia (KSI). The data was collected by distributing questionnaires to 50 respondents using a saturated sampling technique, where all members of the population were sampled, using multiple linear regression testing with the help of the SPSS application. The results of the study indicate that organizational commucation has a positive and significant effect on employee performance. The work environment has a positive and significant effect on employee performance